Asymptomatic Parasitic Worm Thelazia callipaeda Infection Found during Phacoemulsification: A Case Report - Xinzhu Chen; Hanmu Guo; Yanting Li; Peirong Lu (Case Reports in Ophthalmology)
Introduction: We report a case of asymptomatic Thelazia callipaeda infection discovered incidentally during phacoemulsification cataract surgery in March 2024. Case Presentation: A 77-year-old male patient presented with complaints of blurred vision. During a slit-lamp examination, trichiasis was observed, but the patient had no foreign body sensation or itching. He was diagnosed with cataract and underwent phacoemulsification cataract surgery. During the surgery, a white, wriggling worm was discovered in the conjunctival sac and removed. It was later identified as Thelazia callipaeda. The surgical eye was thoroughly washed and received anti-inflammatory medication postoperatively. No recurrence or new symptoms were reported during the 3-month follow-up period. Conclusions: Thelazia callipaeda infection can be asymptomatic and incidentally discovered. A detailed preoperative examination, such as turning over the upper and lower eyelids to check the conjunctival sac, is necessary before the surgery. When a worm is discovered during surgery, it is crucial to remove it completely and thoroughly clean and disinfect the conjunctival sac. Introduction: We report a case of asymptomatic Thelazia callipaeda infection discovered incidentally during phacoemulsification cataract surgery in March 2024. Case Presentation: A 77-year-old male patient presented with complaints of blurred vision. During a slit-lamp examination, trichiasis was observed, but the patient had no foreign body sensation or itching. He was diagnosed with cataract and underwent phacoemulsification cataract surgery. During the surgery, a white, wriggling worm was discovered in the conjunctival sac and removed. It was later identified as Thelazia callipaeda. The surgical eye was thoroughly washed and received anti-inflammatory medication postoperatively. No recurrence or new symptoms were reported during the 3-month follow-up period. Conclusions: Thelazia callipaeda infection can be asymptomatic and incidentally discovered. A detailed preoperative examination, such as turning over the upper and lower eyelids to check the conjunctival sac, is necessary before the surgery. When a worm is discovered during surgery, it is crucial to remove it completely and thoroughly clean and disinfect the conjunctival sac.